Increasing incidence of Plasmodium ovale and persistent reporting of Plasmodium vivax in imported malaria cases: an analysis of 9-year surveillance data in four areas of China - Wang, Xiaoxiao; Xu, Wenjie; Luo, Fei; Lin, Kangming; Zhang, Tao; Yao, Linong; Zhang, Xuan; Zhang, Jiaqi; Auburn, Sarah; Wang, Duoquan; Ruan, Wei (Frontiers in Public Health, 2023)
Background This study aimed at exploring the epidemiological pattern of imported malaria in China before malaria elimination in 2021, to provide evidence-based data for preventing malaria re-establishment in China. Methods Nine-year surveillance data on imported malaria in four provinces (Anhui, Chongqing, Guangxi, and Zhejiang) between 2011 and 2019 were thoroughly collected and analyzed. Results A quite stable trend in imported malaria cases between 2011 and 2019 was observed. In total, 6064 imported patients were included. Plasmodium falciparum was the most frequently reported species (4575, 75.6%). Cases of malaria were most frequently imported from West Africa (54.4%). We identified an increasing trend in P. ovale and a persistence of P. vivax infections among the cases of malaria imported from West Africa. Most patients (97.5%) were 20–59 years old. Among imported malaria infections, the main purposes for traveling abroad were labor export (4914/6064, 81.0%) and business trips (649, 10.7%). Most patients (2008/6064, 33.1%) first visited county-level medical institutions when they sought medical help in China. More patients were diagnosed within 3 days after visiting Centers for Disease Control and Prevention (CDCs) or entry–exit quarantine facilities (EQFs) (1147/1609, 71.3%) than after visiting medical institutions (2182/3993, 54.6%). Conclusion Imported malaria still poses a threat to the malaria-free status of China. County-level institutions are the primary targets in China to improve the sensitivity of the surveillance system and prevent the re-establishment of malaria. Health education should focus on exported labors, especially to West and Central Africa. Increasing trend in P. ovale and persistence of P. vivax infections indicated their underestimations in West Africa. Efficient diagnostic tools and sensitive monitoring systems are required to identify Plasmodium species in Africa.